2004
DOI: 10.1080/09709274.2004.11905739
|View full text |Cite
|
Sign up to set email alerts
|

The Nigerian Oil Industry: Environmental Diseconomies, Management Strategies and the Need for Community Involvement

Abstract: The paper advances the view that environmental diseconomies occasioned by oil industry activities in Nigeria have to a large extent contributed to the lingering crisis in the Niger Delta area, where the bulk of the country's oil and gas is produced. Against this background, the framework for environmental policy and strategies adopted by oil operators is reviewed. It is revealed that the role which communities could play towards minimising negative environmental incidents and related social crises, has been la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This situation was accentuated by the failure to recognize the local community as a stakeholder of the oil industry. Local communities were for years perpetually marginalized and excluded, while they continued to bear the full brunt of oil production (see for example Orubu et al, 2004). As a consequence, communities' perceptions of the Nigerian state, the oil industry and oil companies took a form in which these institutions are seen as antagonists to be confronted.…”
Section: Factors Limiting the Impact Of Corporate-community Relationsmentioning
confidence: 99%
“…This situation was accentuated by the failure to recognize the local community as a stakeholder of the oil industry. Local communities were for years perpetually marginalized and excluded, while they continued to bear the full brunt of oil production (see for example Orubu et al, 2004). As a consequence, communities' perceptions of the Nigerian state, the oil industry and oil companies took a form in which these institutions are seen as antagonists to be confronted.…”
Section: Factors Limiting the Impact Of Corporate-community Relationsmentioning
confidence: 99%
“…In addition, the performance of these activities are within the capacity and power of the OPC and Nigeria's government respectively, therefore making the OPC and the Nigerian government the two key stakeholders within the NOGI (Idemudia, 2009). However, Osobajo and Moore (2017), and Orubu et al (2004) asserted that it is imperative to recognise community involvement within the NOGI. This is because all onshore operations and activities are performed within the communities situated in the Niger Delta region (Omofonmwan and Odia, 2009;Eweje, 2006;Frynas, 2001;Ikelegbe, 2001).…”
Section: An Overview Of the Nigeria Oil And Gas Industry (Nogi)mentioning
confidence: 99%
“…The extent of the impact on the study area where oil exploitation is largely offshore can best be imagined. Orubu et al, (2004) share this view when they reported that massive oil spills occurring in the riverine areas have done untold damage to the aquatic ecosystem, particularly in the mangrove swamp forest zone.…”
Section: Oil Spillagementioning
confidence: 95%